Increasing Teacher and Student Interaction Through Storytelling Culture At the Early Childhood Education (PAUD) in the District Purwakarta - Enjang, Enjang; Adiyanti, Nita (International Conference on Islamic Studies, 2022)
The relationship between teachers and students is felt to be less harmonious and even cold, especially when in the learning process the teacher uses an unpleasant method. The storytelling method is one way to increase interaction between teachers and students because its use is very easy and flexible, then interesting with delivery according to the theme. In addition, it can preserve a culture that is almost extinct. The purpose of this study is to describe the increase in teacher and student interaction through storytelling models or methods in Purwakarta Regency. The method that the researcher uses is a qualitative ethnographic method. Using Interactive data analysis. Data obtained through observations, observations, interviews, and documentation. From this research, it is known that the increase in interaction between teachers and students can be better established so that every learning carried out will be easier, warmer and more enjoyable, especially using interactive storytelling methods.